A high-frequency modeling of AC motor in a frequency range from 40 Hz to 110 MHz - Miloudi, Houcine; Miloudi, Mohamed; Gourbi, Abdelkader; Bermaki, Mohammed Hamza; Bendaoud, Abdelber; Zeghoudi, Abdelhakim (Національний технічний університет "Харківський політехнічний інститут", 2022)
Most electromagnetic compatibility models developed for the study of three-phase induction machines are generally valid for low and medium frequencies (<< 1 MHz). This frequency limit seems to be too restrictive for the overall study of conducted electromagnetic interference. In this paper, the model is using the proposed model and compared with experimental results in low and medium frequency. And then, the high-frequency modeling of induction motor is presented new method based on transfer function model. The proposed methodology is verified on an experimental and simulation, it’s suitable for prediction of the terminal overvoltage analysis and electromagnetic interference problems and common-mode and differential-mode currents. The novelty of the work consists to develop an improved high-frequency motor model based on transfer function to represent the motor high-frequency behavior for frequency-domain analyses in the frequency range from 40 Hz up to 110 MHz .The purpose of this work is to study the common-mode impedance and the differential-mode impedance of AC motor. The determination of these impedances is done for firstly both common and differential modes at low and medium frequency, and then common-mode and differential-mode characteristics at high frequency. Methods. For the study of the path of common-mode and differential-mode currents in typical AC motor (0.25 kW, 50 Hz) an identification method in high frequency for induction motor has been proposed based on the transfer function in differential-mode and common-mode configuration. The low and medium frequency model were presented in the first time based on equivalent circuit of electrical motor. Then, the common-mode and differential-mode impedances were defined in high frequency using asymptotic approach. This motor was studied by MATLAB Software for simulation and also experimental measurements. Results. All the simulations were performed using the mathematical model and the results obtained are validated by experimental measurements performed in the University of the Federal Armed Forces Hamburg in Germany. The obtained results of common-mode and differential-mode at low frequency, medium and high frequency are compared between simulation and experiment.

Більшість моделей електромагнітної сумісності, розроблених для дослідження трифазних асинхронних машин, загалом застосовні для низьких та середніх частот (<<1 МГц). Ця частотна межа здається надто суворою для загального вивчення кондуктивних електромагнітних перешкод. У цій статті запропонована модель використовується і порівнюється з експериментальними результатами за низької та середньої частоти. Потім представлений новий метод високочастотного моделювання асинхронного двигуна, що базується на моделі передавальної функції. Запропонована методологія перевірена експериментально та за допомогою моделювання, вона придатна для прогнозування аналізу перенапруг на клемах та проблем електромагнітних перешкод, а також синфазних та диференціальних струмів. Новизна запропонованої роботи полягає у розробці вдосконаленої моделі високочастотного двигуна на основі передавальної функції для представлення високочастотної поведінки двигуна для аналізу частотної області в діапазоні частот від 40 Гц до 110 МГц. Мета роботи полягає у вивченні синфазного імпедансу та диференціального імпедансу двигуна змінного струму. Визначення цих імпедансів виконується спочатку для синфазних та диференціальних мод на низькій та середній частоті, а потім для синфазних та диференціальних характеристик на високій частоті. Методи. Для дослідження шляху синфазних та диференціальних струмів у типовому двигуні змінного струму (0,25 кВт, 50 Гц) було запропоновано метод ідентифікації на високій частоті для асинхронного двигуна, заснований на передавальній функції у конфігураціях диференціального та синфазного режимів. Вперше представлена низько- та середньочастотна модель на основі схеми заміщення електродвигуна. Потім синфазний та диференціальний імпеданси визначені на високій частоті з використанням асимптотичного підходу. Цей двигун був вивчений програмним забезпеченням MATLAB для моделювання та експериментальних вимірювань. Результати. Все моделювання виконано з використанням математичної моделі, а отримані результати підтверджені експериментальними вимірами, проведеними в Університеті федеральних збройних сил у Гамбурзі, Німеччина. Отримані результати синфазного та диференціального режиму на низькій частоті, середній та високій частоті порівнюються між моделюванням та експериментом.
Keywords: AC motor; differential-mode; common-mode; electromagnetic interference; high frequency; двигун змінного струму; диференціальний режим; синфазний режим; електромагнітні завади; висока частота